Synthesis and characterization of new aromatic polyesters containing biphenyl side groups - Honkhambe, Pandurang N.; Avadhani, C. V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2007)
Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50: 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4-isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the polyesters were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidmone. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. WAXD measurements indicated that all the polyesters and copolyesters were amorphous in nature. Glass transition temperature of polyesters were in the range 198-256 degrees C, while the initial degradation temperature of polyesters were in the range 444-481 degrees C. Copolyesters derived from BBHPE exhibited improved solubility and higher glass transition temperatures compared to the corresponding polyesters based on BPA. (c) 2007 Wiley Periodicals, Inc.
Keywords: Aromatic polyesters; biphenyl side groups

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Synthesis and characterization of organo-soluble poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Honkhambe, Pandurang N.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
Poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant pentadecyl chains were synthesized by polycondensation of each of the two bisphenol monomers viz, 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl] ethane and 1,1-bis(4-hydroxyphenyl)-3-pentadecyl cyclohexane with activated aromatic dihalides namely, 4,4'-difluorobenzophenone, and 1,3-bis(4-fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene, in the presence of anhydrous potassium carbonate. Polymers were isolated as white fibrous materials with inherent viscosities and number average molecular weights in the range 0.70-1.27 dL g(-1) and 76,620-1,36,720, respectively. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were found to be soluble at room temperature in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, and pyridine and could be cast into tough, transparent, and flexible films from their solutions in chloroform. Wide angle X-ray diffraction patterns exhibited a broad halo at around 2 theta = similar to 19 degrees indicating that the polymers containing pentadecyl chains were amorphous in nature. In the small-angle region, diffuse reflections of a typically layered structures resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss, obtained from TG curves, for poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 416-459 degrees C, indicating their good thermal stability. A substantial drop in glass transition temperatures (68-78 degrees C) was observed for poly(ether ether ketone) s and poly(ether ether ketone ketone) s due to ``internal plasticization'' effect of flexible pendant pentadecyl chains. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 3689-3695, 2011
Keywords: alkyl side-chain; Cashew nut shell liquid; CNSL; pentadecyl; poly(arylene ether)s; poly(ether ketone)s; polyethers; renewable

Synthesis and characterization of poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant biphenyl and naphthyl groups - Honkhambe, Pandurang N.; Dhamdhere, Neelam A.; Tawade, Bhausaheb V.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
New poly(ether ether ketone)s (PEEKs) and poly(ether ether ketone ketone)s (PEEKKs) containing pendant biphenyl and naphthyl groups were synthesized by nucleophilic substitution reaction of each of the four bisphenols viz., 1-(4- biphenylyl)- 1,1- bis(4- hydroxyphenyl) ethane, 1-(4- biphenylyl)- 1,1- bis(3- methyl, 4- hydroxyphenyl) ethane, 4,4'-[1-(2- naphthalenyl) ethylidene] bis-phenol and 4,4'-[1-(2- naphthalenyl) ethylidene] bis-3-methylphenol with 4,4'- difluorobenzophenone and 1,3- bis(4- fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene in the presence of anhydrous potassium carbonate. Inherent viscosities and number-average molecular weights of polymers were in the range of 0.42-0.86 dl/g and 2.40-7.55 x 10(4), respectively. PEEKs and PEEKKs were amorphous in nature and were readily soluble in a wide range of organic solvents and could be cast into flexible and tough films from chloroform solution. Glass transition temperature of PEEKs and PEEKKs were in the range of 180 degrees C -200 degrees C. T-10 values of PEEKs and PEEKKs were in the range of 424 degrees C-512 degrees C in nitrogen atmosphere, indicating their good thermal stability.
Keywords: biphenyl; bisphenol; naphthyl; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability